2006
DOI: 10.1007/s11096-005-2221-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Use of Complementary and Alternative Medicine among British Undergraduate Pharmacy Students

Abstract: The knowledge about and use of CAM is widespread among this group of future health care professionals and the students also expressed a strong interest in the topic. In-depth studies on the knowledge and use of CAM among other health care professionals and among ethnic minorities are urgently needed and may help to better manage the treatment of minor disorders as well as chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
29
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 14 publications
(15 reference statements)
10
29
1
1
Order By: Relevance
“…Almost all students expressed the importance of being knowledgeable and trained in CAM in order to advise patients. 13 Positive attitudes toward CAM have also been described in pharmacy students in other countries 14,15 and among undergraduate students across different health care professions. 11,12,16,17 In a study by Lie et al, firstand second-year US medical students' attitudes toward CAM, CAM use, and CAM information-seeking behavior at the University of California-Irvine were previously reported using the same methodology.…”
Section: Discussionmentioning
confidence: 97%
“…Almost all students expressed the importance of being knowledgeable and trained in CAM in order to advise patients. 13 Positive attitudes toward CAM have also been described in pharmacy students in other countries 14,15 and among undergraduate students across different health care professions. 11,12,16,17 In a study by Lie et al, firstand second-year US medical students' attitudes toward CAM, CAM use, and CAM information-seeking behavior at the University of California-Irvine were previously reported using the same methodology.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have been conducted in developed countries to determine the knowledge and attitude of medical, pharmacy and nursing students and academic staff on CAM, which have shown that students have a high level of interest in and positive attitude towards CAM [12,13,14,15,16,17,18]. In contrast, data from the developing countries is limited [19], where traditional medicine is widely practiced [6].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] The majority of medical and pharmacy students surveyed welcomed the inclusion of CAM education in the curricula; nursing students were less enthusiastic. 6,[14][15][16][17] The increased use of CAM worldwide requires that consideration be given to the integration of CAM into health professions education. However, incorporation of CAM into health professions curricula is handled differently by institutions and countries.…”
Section: Introductionmentioning
confidence: 99%